Respuesta :

Answer: The answers are:

6 + 2 = 8

4 + (-1) = 3

Step-by-step explanation:

Add 6 by 2.

Solve for X.

4 + X = 3

To find X, we use the integer rule. We can use this:

Positive and Positive =  Positive

Negative and Negative = Negative

Positive and Negative = Both (It depends if the negative or positive is larger than the other)

For this problem, we can use: Positive and Negative = Both.

If we look at the chart, we can see 4 and 3. How can we get 4 + ? = 3? We can use the integer, -1. Since we said, Positive and Negative = Both, we must compare the positive-addend (4) by the negative-addend (-1).

4 is greater than -1

4 > -1

Therefore, X equals -1.

4 + (-1) = 3

Answer: 8, -1

Step-by-step explanation:

The table shows some addition problems.  Each column is its own problem, with the first two rows being addends and the bottom row being the sum.  Thus, simply do 6+2 to get the first blank(left-to-right), 8.  Then, do 4+x=3 to get the second blank, or -1.

Hope it helps :D

ACCESS MORE